Grassland growth response to drought in dryland Inner Mongolia: insights from a two-decade analysis - Miao, Lijuan; Yu, Zhiwei; Zhu, Xiaorui; Agathokleous, Evgenios; Bao, Gang; Iqbal, Pervaiz; Liu, Qiang (Environmental research letters, 2025)
The frequency of extreme drought events is increasing, significantly impacting ecosystems worldwide. In China, the grasslands of dryland Inner Mongolia provide a vital ecological resource, highlight the urgent need to understand their response to drought in these arid regions. We investigate vegetation dynamics and soil moisture fluctuations across three grassland types—meadows, typical grasslands, and desert grasslands—utilizing solar-induced fluorescence (SIF), normalized difference vegetation index (NDVI), and soil moisture data from 2001 to 2020. By employing event coincidence analysis and the maximum coincidence rate, we quantified the grasslands’ responses to drought events. Our findings indicate a significant upward trend in SIF across all grassland types over the past two decades, while NDVI and soil moisture levels remained relatively stable. Under drought conditions, the probability of grassland degradation ranged from 40% to 60%. Notably, desert grasslands exhibited a considerably slower response rate compared to other grassland types, while meadow grasslands responded the fastest to drought; however, all grassland types displayed a response delay of 1–2 months. When soil moisture levels fell below −1.8 standard deviations (STDs), a reversal in grassland response patterns was observed, particularly in meadow grasslands, which showed a substantial increase in response probability. At soil moisture levels below −2.4 STD, this probability stabilized at approximately 90%, significantly higher than that of other grassland types. These insights provide a vital basis for understanding and mitigating drought impacts on resilient grassland ecosystems under climate change.